Non-invasive Medical Devices for Detection and Monitoring within Healthcare - Priefer, Ronny (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
Biosensors, especially non-invasive ones, are an area of extreme importance and fantastic advancements. As nanotechnology continually becomes more and more refined, its applications in a multitude of areas also grow. One area that has seen an explosion of innovations is healthcare. Such biosensors have allowed for the diagnosis, monitoring, and even treatment of a myriad of different disease states. This reprint highlights many of the past, current, and potential future advancements.